Do Performance Appraisal, Compensation Andjob Satisfaction Influence Employees Loyalty Of Generation Y? - Neela Osman; Dedi Purwana; Ari Saptono (Journal of Business and Behavioural Entrepreneurship, 2017)
GenerationY is the work force of the future and now the number is dominating the industry.The increasing number of employees of generation Y becomes a separate problem for the company in meeting the availability of young professional workforce. The research aims to investigate effect of performance appraisal, compensation and job satisfaction to loyalty of generation Y.Method used in this study was quatitative. The research sample was 117 students. Data was anaysed using Structural Equation Modeling (SEM). This study reveals there are a positive relationship between performance appraisal with job satisfaction, compensation with job satisfaction and job satisfaction on loyalty.